Evolution of Customer Satisfaction, Delight, and Retention Drivers in the Service Industry: A Bibliometric Analysis - Niken Ayu Rahmawati; Tony Wijaya; Agung Utama (LifeSciFi, 2026)
Increasing dynamics of the global service industry require a shift in focus from mere customer satisfaction toward deeper emotional engagement and customer experience to sustain loyalty. The aim of this research is to map the intellectual structure and development of studies related to customer satisfaction, customer experience, and customer delight within the service marketing literature. The method employed is a bibliometric approach based on 271 documents retrieved from the Scopus database, analyzed using VOSviewer through keyword co-occurrence analysis to identify major clusters and research trends. The results reveal five main clusters encompassing cognitive evaluation dimensions, customer experience, emotional and service interaction, brand perception, and long-term relational loyalty. The findings also indicate a paradigm shift toward experience-based and personalization-oriented approaches, with customer experience acting as a key mediating construct between service quality and customer loyalty, while customer delight remains relatively underexplored. In conclusion, the literature reflects a transition from a transactional model to an emotionally driven experience-based model. The implications suggest that service organizations should prioritize strategies focused on creating emotionally engaging experiences to enhance sustainable customer loyalty.